Impact of Working Environment on Less Productivity in RMG Industries: A Study on Bangladesh RMG Sector (Global Journal of Management and Business Research, 2015)
The readymade garments industry (RMG) sector acts as the backbone of Bangladesh economy and is considered as a catalyst for the development of the country. Despite having epic growth of the RMG sector, and its bright prospects, challenges are still there. One of the biggest challenges currently faced by RMG industries of Bangladesh is to ensure better working conditions for the millions of garment workers which might have salient impacts in accelerating productivity to compete in global export market.
Keywords: orking environment; less productivity; rmg sector; multiple regression; anova; hypothesis